Regulatory Effects of Combined Dietary Supplementation With Essential Oils and Organic Acids on Microbial Communities of Cobb Broilers - Qiao, Jiayun; Shang, Zhiyuan; Liu, Xuejiao; Wang, Kewei; Wu, Zhiwei; Wei, Qing; Li, Haihua (Frontiers in Microbiology, 2022)
The emergence and spread of antibiotic resistance genes in pathogenic microorganisms have resulted in many countries restricting the use of antibiotics as growth promoters in animal feed. The combined use of essential oils and organic acids can help maintain intestinal health, improve animal growth performance, and alleviate the negative effects of banned antibiotics for certain economically important animals. Although the modes of action for the combined dietary supplementation of essential oils and organic acids such as thymol-citric acid (EOA1) and thymol-butyric acid (EOA2) remain unclear, it is speculated that their activities are achieved through beneficial modulation of gastrointestinal microbial communities and inhibition of pathogen growth. In this study, 16S rDNA amplicon sequencing was used to analyze the effects of treatment with EOA1 and EOA2 on the jejunal, cecal, and fecal microbial communities of Cobb broilers while also evaluating effects over different broiler ages. The intestinal microbial communities of broilers developed with increasing age, and Lactobacillus gradually came to dominate the intestinal communities of treated broilers. Further, the microbial communities of feces were more complex than those of the jejuna and ceca. We systematically elucidate that the longitudinal changes in the intestinal microbial communities of Cobb broiler chickens at different ages. Meanwhile, we found that the addition of EOA1 or EOA2 to the diet: 1) inhibited the proliferation of Ralstonia pickettii and Alcaligenaceae in the jejuna on day 28, 2) promoted the colonization and growth of beneficial bacteria such as Lactobacillus, Clostridia, and Bacteroidia at various growth stages, and 3) enriched the abundance of certain microbiota functions, including biological pathways related to metabolism (e.g., enzyme families). Taken together, the results of this study demonstrate that EOA1 and EOA2 dietary supplementation can affect various microbial metabolic pathways related to the metabolism and absorption of nutrients via regulation of the intestinal microbial community structures of Cobb broilers, while also playing an important role in host growth.